Bluegrass Renaissance : The History and Culture of Central Kentucky, 1792-1852 - Rowland, Daniel B. (Daniel Bruce), 1941-; Klotter, James C. (Book collections on Project MUSE., 2012)
Originally established in 1775 the town of Lexington, Kentucky grew quickly into a national cultural center amongst the rolling green hills of the Bluegrass Region. Nicknamed the ""Athens of the West, "" Lexington and the surrounding area became a leader in higher education, visual arts, architecture, and music, and the center of the horse breeding and racing industries. The national impact of the Bluegrass was further confirmed by prominent Kentucky figures such as Henry Clay and John C. Breckinridge. The Idea of the Athens of the West: Central Kentucky in American Culture, 1792-1852